Pro-apoptotic carboxamide analogues of natural fislatifolic acid targeting Mcl-1 and Bcl-2. Issue 7 (1st April 2020) - Gapil Tiamas, Shelly; Daressy, Florian; Abou Samra, Alma; Bignon, Jérome; Steinmetz, Vincent; Litaudon, Marc; Fourneau, Christophe; Hoong Leong, Kok; Ariffin, Azhar; Awang, Khalijah; Desrat, Sandy; Roussi, Fanny
Graphical abstract: Abstract: A library of 26 novel carboxamides deriving from natural fislatifolic acid has been prepared. The synthetic strategy involved a bio-inspired Diels-Alder cycloaddition, followed by functionalisations of the carbonyl moiety. All the compounds were evaluated on Bcl-xL, Mcl-1 and Bcl-2 proteins. In this series of cyclohexenyl chalcone analogues, six compounds behaved as dual Bcl-xL/Mcl-1 inhibitors in micromolar range and one exhibited sub-micromolar affinities toward Mcl-1 and Bcl-2. The most potent compounds evaluated on A549 and MCF7 cancer cell lines showed moderate cytotoxicities.